2014
DOI: 10.1080/10228195.2013.857362
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic analysis of the structure of Yoruba numerals

Abstract: This paper adopts a descriptive approach in analyzing the counting system of the Yoruba language. It explains the technicalities of its arithmetical involvements which appear to have been contributing to the difficulty often encountered in its learning. The study relies on three major sources in gathering data for the descriptive analysis, namely, compilation of relevant list of Yoruba numerals, the researcher's intuitive knowledge of the language coupled with his training as a linguist, and a search of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…While the word meter has been substituted as mita in the translation instead of ibuso, it is still acceptable under the premise of lexical borrowing [53], [54]. However, the that occurs in the translation of Yoruba numbers such as three hundred to odotarun meta instead of orundin nirinho completely contravenes either of the Yoruba numerals formation -the cardinal (asoye or onkaye) or the ordinal (asopo or onkapo) system [55], [56]. We argue that the word odotarun does not exist in the Yoruba language.…”
Section: ) Libretranslatementioning
confidence: 99%
“…While the word meter has been substituted as mita in the translation instead of ibuso, it is still acceptable under the premise of lexical borrowing [53], [54]. However, the that occurs in the translation of Yoruba numbers such as three hundred to odotarun meta instead of orundin nirinho completely contravenes either of the Yoruba numerals formation -the cardinal (asoye or onkaye) or the ordinal (asopo or onkapo) system [55], [56]. We argue that the word odotarun does not exist in the Yoruba language.…”
Section: ) Libretranslatementioning
confidence: 99%
“…The study by [16], shows that Yorùbá numeral maintains a VCV (disyllabic) open syllabic structure while English numeral has a monosyllabic closed syllabic structure CVC for numeral 1, 5, 9 and 10, CVCC for 6, and VC for 8. The study also agreed with [14] and [12] that, numerals 200, 300 and 400 are basic in Yorùbá numeral system while numerals 500, 700 and 900 are derived through a combination of subtraction and multiplication whereas 600, 800 and 1000 are derived by multiplying 200 by 3, 4, and 5 respectively.…”
Section: Related Workmentioning
confidence: 99%
“…The invention of a numeration system is regarded as one of the great accomplishments of man, and the Hindu-Arabic, simply Arabic (0,1,2,3,4,5,6,7,8,9) is one of the most widely used numerals (Hess, 1970). Numeral system greatly assists man in expressing his communication needs (Agbeyangi et al, 2016;Babarinde, 2013), and also serve as an important tool in language pedagogy, historical linguistics, comparative study of African languages and computational linguistics (Babarinde, 2013). However, according to Babarinde (2013), numeral system is an endangered area being identified in language use and study.…”
Section: Introductionmentioning
confidence: 99%
“…Numeral system greatly assists man in expressing his communication needs (Agbeyangi et al, 2016;Babarinde, 2013), and also serve as an important tool in language pedagogy, historical linguistics, comparative study of African languages and computational linguistics (Babarinde, 2013). However, according to Babarinde (2013), numeral system is an endangered area being identified in language use and study. Affirming Babarinde (2013) statement, Mbah et al (2014) reported that in no distant time, the traditional number system of the African indigenous counting system might lose its contact with the new generation, due to the fast influence of the western decimal numeral system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation